If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7 = -14x Solving -7 = -14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14x' to each side of the equation. -7 + 14x = -14x + 14x Combine like terms: -14x + 14x = 0 -7 + 14x = 0 Add '7' to each side of the equation. -7 + 7 + 14x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + 14x = 0 + 7 14x = 0 + 7 Combine like terms: 0 + 7 = 7 14x = 7 Divide each side by '14'. x = 0.5 Simplifying x = 0.5
| -70=14 | | -4/9=-3/2 | | y+5=15 | | 9x+x-5x+x= | | 3x^2+12x-21=0 | | 7(y-8)= | | 3x^2+12-21=0 | | -9x=4-(-15) | | 3x^2-12-21=0 | | 4g=-24 | | 5(5y-6)=15y | | 2x=5+3(4x-5) | | -5(9a+8)= | | -4(x+2)+11x= | | -2(2x-5)=0.50(6x+3) | | 3y+y-12y= | | x^2-16x+4=0 | | y=6(-3)+23 | | y=(-3)+23 | | 8(9z)= | | 0.25y+6=-3 | | x/15=-11+2 | | 9(x+6)=-3(x-39) | | 2(n-3)+6=4n-10 | | r^5-8r^2=0 | | 4x-4+2x+9= | | -9-5=4x+4x+4-3x | | -x+3(6x+23)=18 | | 4(x-5)=3(2-x) | | 3(6x-3)-8(x-2)= | | 9(x+8)=8x+74 | | 7(2z+4)-1= |